Fry and Larvae of Fishes and Crustaceans in Coastal Marine Waters of Negros Oriental, Negros Island, Philippines - Alcala, Angel C.; Cabanban, A. S. (Silliman Journal, 2024)
One hundred and thirty-two species of fish belonging to 55 families and one order and ten species of crustaceans belonging to five families and three orders were found associated with Chanos chanos fry from seven sampling stations on the coast of Negros Oriental province, Negros Island, Philippines during a 12-month period from December 1984 through November 1985. About two-thirds of these species are used for food.